The impact of inbound logistics activities on the operational performance of the postal services organization in South Africa - Tabeni, Mvelo (Rhodes University, Faculty of Commerce, Investec Business School, 2006)
Introduction and Relevant Details: This research investigates the impact of inbound logistics' activities on the operational performance of the business within the branches of the South African Post Office (SAPO) in the Eastern Cape Province. The study basically hypothesises a statistically significant positive correlation between inbound logistics' activities and the operational performance of the business with regards to revenue generation and operational costs in particular. A sample of 100 branch offices was randomly selected. A 50-item questionnaire was administered by mail to the branches to collect the data during September 2005, and statistical tests for correlation were conducted on at least five dependent variables; stock procurement costs, effects on revenue, number of stock variation occurrences, order variation occurrences and the stock holding effects. Results of Data Analysis: The results of 88 respondents (88%) showed the existence of the significant positive relationship between the inbound logistics activities and the operational performance of the business at the South African Post Office branches as proposed by the study. The Spearman Rank Correlation tests were above 0.7 for most of the tested variables, showing a strong relationship. The inbound logistics' activities were also found to be positively correlated to revenue generation as well as to the operational expenses of the business. Conclusion and Recommendations: The findings allowed the researcher to conclude also that whatever improvements are made to the inbound logistics will also impact on the operational performance of the business, while failures in the inbound logistics will do so negatively. Business endeavours to maximise revenue and minimise costs are directly affected by the inbound logistics' activities. The branches of the SAPO seemed to be dissatisfied with most of the services rendered by the Supply Distribution Centre (SOC) of the SAPO, and such services have negatively affected the achievement of revenue targets at the branches as well as the operational costs. Holistic approaches to developing positive perceptions in the branches together with improving service activities at the SOC are recommended. Collaborative initiatives between branches and the SOC, reviewing the lead-times and the establishment of proper structures to handle supply chain queries, enhanced by information system technology to provide accurate and up-to-date information to branches and related parties about stock order issues are required . Areas of further research highlighted include the inbound logistics' activities of the SOC and the effectiveness of company policies as a guide to Supply Chain Management (SCM).
Keywords: South African Post Office Postal service -- South Africa Business logistics Business logistics -- Cost effectiveness Delivery of goods -- Management Physical distribution of goods Customer services -- Management